Genetic Susceptibility for Atrial Fibrillation in Patients Undergoing Atrial Fibrillation Ablation. (March 2020) - Shoemaker, M. Benjamin; Husser, Daniela; Roselli, Carolina; Al Jazairi, Meelad; Chrispin, Jonathan; Kühne, Michael; Neumann, Benjamin; Knight, Stacey; Sun, Han; Mohanty, Sanghamitra; Shaffer, Christian; Thériault, Sébastien; et al.
Abstract : Background: Ablation is a widely used therapy for atrial fibrillation (AF); however, arrhythmia recurrence and repeat procedures are common. Studies examining surrogate markers of genetic susceptibility to AF, such as family history and individual AF susceptibility alleles, suggest these may be associated with recurrence outcomes. Accordingly, the aim of this study was to test the association between AF genetic susceptibility and recurrence after ablation using a comprehensive polygenic risk score for AF. Methods: Ten centers from the AF Genetics Consortium identified patients who had undergone de novo AF ablation. AF genetic susceptibility was measured using a previously described polygenic risk score (N=929 single-nucleotide polymorphisms) and tested for an association with clinical characteristics and time-to-recurrence with a 3 month blanking period. Recurrence was defined as >30 seconds of AF, atrial flutter, or atrial tachycardia. Multivariable analysis adjusted for age, sex, height, body mass index, persistent AF, hypertension, coronary disease, left atrial size, left ventricular ejection fraction, and year of ablation. Results: Four thousand two hundred seventy-six patients were eligible for analysis of baseline characteristics and 3259 for recurrence outcomes. The overall arrhythmia recurrence rate between 3 and 12 months was 44% (1443/3259). Patients with higher AF genetic susceptibility were younger ( P <0.001) and had fewer clinical risk factors for AF ( P =0.001). Persistent AF (hazard ratio [HR], 1.39 [95% CI, 1.22–1.58]; P <0.001), left atrial size (per cm: HR, 1.32 [95% CI, 1.19–1.46]; P <0.001), and left ventricular ejection fraction (per 10%: HR, 0.88 [95% CI, 0.80–0.97]; P =0.008) were associated with increased risk of recurrence. In univariate analysis, higher AF genetic susceptibility trended towards a higher risk of recurrence (HR, 1.08 [95% CI, 0.99–1.18]; P =0.07), which became less significant in multivariable analysis (HR, 1.06 [95% CI, 0.98–1.15]; P =0.13). Conclusions: Higher AF genetic susceptibility was associated with younger age and fewer clinical risk factors but not recurrence. Arrhythmia recurrence after AF ablation may represent a genetically different phenotype compared to AF susceptibility. Abstract : Supplemental Digital Content is available in the text.